Education on Making Processed Snack Food Products from Local Ingredients to Increase Family Income - Widalicin Januarty; Elisabeth Nainggolan; Susan Grace V Nainggolan; Ahmad Nizam; Sipnarong Kanchawongpaisan; Muhammad Hafiz Abd Rashid; Haykal Riskyandana (Eastasouth Journal of Effective Community Services, 2025)
The limited economic capacity of rural families often stems from minimal knowledge about local resource utilization and weak home-based business management. This program aimed to enhance family income through education on the production of processed snack foods using locally available ingredients. A service-learning and participatory empowerment approach was implemented with 40 housewives, youth representatives, and micro-entrepreneurs. Training included product innovation, hygiene practices, packaging techniques, and basic financial management. Results indicated a 65% increase in participants’ knowledge of snack processing techniques, and 75% began producing or selling snack products within one month post-training. Proper education accompanied by mentoring can effectively transform local agricultural commodities into marketable food products, thereby contributing to household income enhancement and sustainable community-based entrepreneurship.